Impact of the content and size of NaCl on dynamic sensory profile and instrumental texture of beef burgers - Rios-Mera J.D. (2020)
The objectives of this study were to determine the effect of reducing the content and size of NaCl on the instrumental texture and dynamic sensory profile, and to determine the temporal drivers of liking (TDL). The reduction of the NaCl content decreased the hardness and chewiness parameters, and affected the dynamic sensory profile of the product. The NaCl reduction (<1.0% NaCl) was related to a higher incidence of the attributes off-flavor and dry. In general, the overall liking was driven by the juicy and tasty attributes, the latter being associated with the presence of the sensory attributes salty and seasoned and the texture parameters hardness and chewiness. According to the results, among the treatments with NaCl reduction, the beef burger added with 1.0% micronized salt stood out, since it did not affect considerably the texture parameters, the dynamic sensory profile during chewing and the consumers' liking. © 2019 Elsevier Ltd